Republic of Estonia : 2002 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Estonia. (IMF Staff Country Reports; Country Report, 2002)
This 2002 Article IV Consultation highlights that Estonia continues to be an outstanding performer among the transition economies reflecting the authorities' continued commitment to market-based reforms, pursuit of sound macroeconomic policies, emphasis on institution building, and a commitment to transparency. In 2001, the Estonian economy showed remarkable resilience given the slowdown in economic activity among its main trading partners. Although growth decelerated somewhat compared with the previous year, the economy grew at a healthy 5.4 percent, driven largely by a pickup in investment demand.